Beginning and rise of the dramatic radio opera in Spain (1953-1959): The example of the “Lady in green” - Blanco Fajardo, Sergio (Hispania Nova, 2023)
The ideologues of the Franco regime discovered the potential of the radio soap opera to represent in its stories and characters the ideals defended by national Catholicism. In this sense, the radio soap opera constructed, through language, signs, symbols and life practices, a female cultural system. This article analyses the first years of dramatic broadcasts on private radio (Cadena SER), specifically, the discourse of the serial “La dama de verde” (The Lady in Green), in order to glimpse the implications of the radio soap opera in the shaping of the social imaginary of women. On the other hand, the appearance of fissures in his discourse created a scope for heterodox readings. To explore these ambiguities and contradictions, we will pay attention to the relationship between audience, discourse, context and a subjective mode of perception.